1995
DOI: 10.1093/infdis/171.3.755
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Parasitologic, And Immunologic Observations Of Patients With Hydrocele And Elephantiasis In An Area With Endemic Lymphatic Filariasis

Abstract: Hydrocele and elephantiasis, major clinical manifestations of bancroftian filariasis, are thought to share a common pathogenesis. The characteristics of 121 patients with hydrocele or elephantiasis in Leogane, Haiti, were compared: 39% of 57 men with hydrocele and 3% of 64 persons with lymphedema of the leg were microfilaria-positive (P < .001). Circulating filarial antigen, presumably from the adult worm, was detected in 15 (43%) microfilaria-negative men with hydrocele and 9 (15%) microfilaria-negative perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
40
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 9 publications
4
40
0
2
Order By: Relevance
“…Antifilarial IgG levels were standardized against a calibrated reference sample generously provided by Dr. Eric Ottesen (formerly of the National Institutes of Health, Bethesda, MD) as previously described. 8,21 IgE assays were performed without prior absorption of IgG. In previous studies of specimens from Haiti, we found no evidence that antifilarial IgG4 interfered with detection of antifilarial IgE.…”
Section: Methodsmentioning
confidence: 64%
See 2 more Smart Citations
“…Antifilarial IgG levels were standardized against a calibrated reference sample generously provided by Dr. Eric Ottesen (formerly of the National Institutes of Health, Bethesda, MD) as previously described. 8,21 IgE assays were performed without prior absorption of IgG. In previous studies of specimens from Haiti, we found no evidence that antifilarial IgG4 interfered with detection of antifilarial IgE.…”
Section: Methodsmentioning
confidence: 64%
“…Assays for antigen-and parasite-specific immunoglobulins were quantified by enzyme-linked immunosorbent assay as previously described. 8,20 Briefly, assays to detect antibody responses to adult filarial antigen (Bpa) were performed using biotinylated monoclonal antibodies (Zymed Laboratories, San Francisco, CA) specific for IgG1, IgG2, IgG3, IgG4, and IgE. Antifilarial IgG levels were standardized against a calibrated reference sample generously provided by Dr. Eric Ottesen (formerly of the National Institutes of Health, Bethesda, MD) as previously described.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also do not account for more recently suggested sources of the observed heterogeneity, including acquired immunity, 10,11 maternally-derived immune tolerance, 12,13 and adult-worm induced or immune-mediated pathology. 14,15 Recent work has indicated that one factor that may systematically explain differences in age-patterns of infection and disease between endemic communities in filariasis is parasite transmission intensity. For example, Michael and Bundy used a mathematical modeling approach to demonstrate that variations in community transmission intensity may, via the generation of exposure-driven acquisition of herd immunity, shape the observed age-patterns of infection (microfilaremia) in endemic communities.…”
Section: Introductionmentioning
confidence: 99%
“…There is also increasing consensus that progression from this stage to symptomatic disease may occur along different pathways for the two most common manifestations of chronic disease, namely lymphodema and hydrocele. 32 For lymphodema, the available evidence suggests that pathogenesis could involve three possible mechanisms. The first is that disease develops as a natural sequel to worminduced physical damage to the lymphatics, which eventually becomes sufficient to reduce the flow of lymph fluid.…”
mentioning
confidence: 99%